Fiction et forme encyclopédique : Wookieepedia, Dragon Ball Wiki et Cie. - Benoît Berthou (Strenae)
Wookieepedia, Final Fantasy Wiki, Dragon Ball Wiki, Memory Alpha, WoWWiki... So many online encyclopedias deal with famous young adult and children’s fiction, through an often vast number of articles, tackling all sorts of subjects (stories, technologies, characters, places, authors, fans...). What can we learn from these sources which try to take fiction seriously, that is to say, to approach the domain of fantasy with tools from a domain of knowledge? Two practices stand out: references to cultural products taking many diverse forms (novels, comics, films, video games...) and the link between the various articles. These two practices show how an expertise regarding a fiction can develop—the ability to situate oneself within an imaginary construction.